2022
DOI: 10.1590/1676-0611-bn-2021-1283
|View full text |Cite
|
Sign up to set email alerts
|

Multi-taxon inventory and landscape characterization in an agrosystem of the Brazilian Midwest targeted for payment for environmental services

Abstract: The replacement of natural landscapes by anthropic environments has led to habitat loss and consequently, to the decline and extinction of many species populations. Several strategies, such as the creation of protected areas (PAs) and payment for ecosystem services have been adopted to mitigate the consequences of this biodiversity crisis. In Rio Verde, Goiás, Brazil, a Water Producer Program (WPP) was established, which provides payment for ecosystem services for the maintenance of riparian vegetation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In particular, the latter authors found that by 2016, only 23% of the municipality was covered with native vegetation (e.g., grassland, forest, and savanna formations). This pattern has been repeated within the Abóbora basin on a smaller scale, where Morais et al (2022) found in 2018 that approximately 21% of the total area of this basin was covered with native vegetation.…”
Section: An Acad Brasmentioning
confidence: 81%
See 2 more Smart Citations
“…In particular, the latter authors found that by 2016, only 23% of the municipality was covered with native vegetation (e.g., grassland, forest, and savanna formations). This pattern has been repeated within the Abóbora basin on a smaller scale, where Morais et al (2022) found in 2018 that approximately 21% of the total area of this basin was covered with native vegetation.…”
Section: An Acad Brasmentioning
confidence: 81%
“…In contrast with previous studies (Siqueira & Faria 2019, Morais et al 2022, the present analysis focused on an even more restricted scale, that is the 50 m buffer around the springs of the study's streams. In 2017, the springs that feed into the Abóbora River had a mean native vegetation cover of approximately 80%.…”
Section: An Acad Brasmentioning
confidence: 98%
See 1 more Smart Citation